A new species and new records of the spider genus Dubiaranea (Araneae, Linyphiidae) from southern Brazil and Uruguay, with an analysis of the potential distribution of the species - Cajade, Manuel; Hagopián, Damián; Rodrigues, Everton N. L.; Guerrero, José C.; Laborda, Álvaro; Simó, Miguel (Zootaxa, 2024)
Dubiaranea magatama Cajade, Hagopián & Rodrigues n. sp. is described from Uruguay, and southern Brazil based on males and females from several types of native forests, and a potential distribution for this species is modeled. The predicted model for this species indicates a Pampean province and southern Atlantic Forest biome distribution. Three variables contributed significantly to the model with positive influence: the spatial component, the proximity to large rivers, and the tree cover. Also, we provide new records of Dubiaranea difficilis (Mello-Leitão 1944) for Uruguay and a model of its potential distribution was performed. It showed that tree cover, the proximity to large rivers, the spatial component and precipitation/evapotranspiration constraints were recovered for the model with positive influence, expanding the potential distribution area previously proposed.